Analysis on the effect of different bracing types and layouts on lateral drift of 30-storey steel framed building subjected to lateral forces using ANSYS - Dushendran, Bala Krisnain (2015)
High-rise steel construction is increasing at an expanding scale and in modern construction stiffness of the structure has become paramount criteria as the building increases in height. However, the aerial threat of wind forces had become a crucial factor to affect the building stiffness. Designers see great danger of this situation and it has led to introduction of bracing system that was often used to provide sufficient lateral stiffness to the structure. The main objective of this study is to determine the effect of different types and orientations of bracing on the frame structure in terms of lateral drift. Finite Element Analysis (FEA) of ANSYS 12.0 software has been used to model 30-storey of 90 m height steel frame building subjected to substantial basic wind speed, or 3-second gust, of 24 meter per second, and wind load of 0.969 kPa. Four types of bracing: X-bracing, Inverted V-bracing, K-bracing and single-diagonal bracing were explored and 84 models of different configurations were run. Prior to limiting the lateral drift, the 84 models were again used to study the effect of changing from using pin connections to a combined pin-moment connections. All the beam and column used is made up of I-beam of structural steel grade S275 and of 3D Spar Link 8 element type. The X-bracing and Inverted V-bracing were relatively known as good in limiting lateral drift with regard to both types and configurations of bracing compared to K-bracing and single diagonal bracing. Meanwhile, changing from using pin connection to a combined pin-moment connections had reduced the lateral drift to about 26% to 48% depending on the type of bracing used.